Downregulation of both gene expression and activity of Hsp27 improved maturation of mouse oocyte in vitro - Cai Ling-Bo; Ma Xiang; Liu Jin-Juan; Cui Yu-Gui; Liu Jia-Yin (BMC, 2010)
Abstract Background Heat shock protein 27 (Hsp27), a member of the small heat shock protein family, is an apoptosis regulator. Our previous proteomic study showed that Hsp27 mainly expressed in human oocyte, and that Hsp27 expression was downregulated in the ovaries derived from women with the polycystic ovary syndrome (PCOS), a well known endocrinal disorder with abnormal apoptotic activity and folliculogenesis. However, the exact effects of Hsp27 downregulation on oocyte development have not yet been clarified. Methods The expression of Hsp27 gene was downregulated in the mouse oocytes cultured in vitro using siRNA adenovirus infection, while the activity of Hsp27 was decreased by microinjection of polyclonal Hsp27 antibody into the cytoplasm of germinal vesicle (GV) oocytes. Oocyte maturation rate was evaluated by morphological observation. Early stage of apoptosis was determined using Annexin-V staining analysis and some critical apoptotic factors and cytokines were also monitored at both mRNA level by real time RT-PCR and protein expression level by immunofluorescence and western blot. Results Hsp27 expressed at high level in maturing oocytes. Infection with AdshHsp27, and microinjection of Hsp27 antibody into GV oocytes, resulted in the improved oocyte development and maturation. Germinal vesicle breakdown (GVBD) rates were significantly increased in two AdshHsp27-treated groups (88.7%, 86.0%) and Hsp27 antibody-injected group (77.0%) when compared with control (76.2% in AdGFP, 64.4% in IgG-injected), respectively. In addition, the rates of metaphase II (MII) development in two AdshHsp27-treated groups (73.8%, 76.4%) and Hsp27 antibody-injected group (67.3%) were higher than that in the controls (59.6% in AdGFP, 55.1% in IgG-injected). We also found that the rates of early stage of apoptosis in Hsp27 downregulated groups (46.5% and 45.6%) were higher than that in control group (34.1%) after 8 h of IVM. Similarly, downregulation of Hsp27 caused a significantly enhanced the expression of apoptotic factors (caspase 8, caspase 3) and cytokines (bmp 15 and gdf 9). Conclusions Downregulation of Hsp27 improved the maturation of mouse oocytes, while increased early stage of apoptosis in oocytes by inducing the activation of extrinsic, caspase 8-mediated pathway.